1998
DOI: 10.1101/gad.12.11.1587
|View full text |Cite
|
Sign up to set email alerts
|

Smad2 transduces common signals from receptor serine–threonine and tyrosine kinases

Abstract: SMAD proteins mediate signals from receptor serine–threonine kinases (RSKs) of the TGF-β superfamily. We demonstrate here that HGF and EGF, which signal through RTKs, can also mediate SMAD-dependent reporter gene activation and induce rapid phosphorylation of endogenous SMAD proteins by kinase(s) downstream of MEK1. HGF induces phosphorylation and nuclear translocation of epitope-tagged Smad2 and a mutation that blocks TGF-β signaling also blocks HGF signal transduction. Smad2 may thus act as a common positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
5
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(206 citation statements)
references
References 38 publications
5
190
5
4
Order By: Relevance
“…HGF and oncogenic ras have been shown to alter TGFb signaling in human breast cancer cells and mouse mammary epithelial cells, respectively (de Caestecker et al, 1998;Kretzschmar et al, 1999). In addition, IFNg can inhibit nuclear translocation of Smad3 in a mutant human fibrosarcoma cell line (Ulloa et al, 1999), which could interfere with TGFb transcriptional responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HGF and oncogenic ras have been shown to alter TGFb signaling in human breast cancer cells and mouse mammary epithelial cells, respectively (de Caestecker et al, 1998;Kretzschmar et al, 1999). In addition, IFNg can inhibit nuclear translocation of Smad3 in a mutant human fibrosarcoma cell line (Ulloa et al, 1999), which could interfere with TGFb transcriptional responses.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous signaling pathways have been shown to converge with the TGFb signaling pathway to modulate its effects. Depending on the cell context, interferon gamma (IFNg), hepatocyte growth factor (HGF), epidermal growth factor (EGF) and oncogenic ras have all been shown to modulate TGFb signaling (de Caestecker et al, 1998;Kretzschmar et al, 1999;Ulloa et al, 1999;ten Dijke et al, 2000;Funaba et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…pT␤-RII contains 1,670 bp of the gene promoter of TGF-␤ receptor type 2 (T␤-RII) (4). cDNA expression plasmid pdn-T␤-RIIcDNA was a gift from Dr. Robert J. Lechleider (NCI) and contains cDNA encoding the dominant-negative form of T␤-RII (17). Semiconfluent HSCs in six-well cell culture plates were transiently transfected using LipofectAMINE reagent (Life Technologies, Grand Island, NY).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, there is increasing evidence for cross-talk between the TGF and the ras signalling pathway, with the observation that SMAD2 can be activated by the HGF-ras-MEK1-ERK1/2 pathway. 124 It has also been demonstrated that TGF can activate ras, and ERK1/2, and that this activity is essential for many of TGF 's actions, including negative growth control. 125,126 Certainly a dominant negative ras mutation can abrogate TGF effects, 127 but whether TGF and ras are on the same pathway or synergistically involved is not known.…”
Section: The Balance Between the Tumour Suppression And Progression Rmentioning
confidence: 99%